Observed Baseline and Future Projection of Royal Belum State Park - Zin Zafirah Husna Mohd; Ju Neng Liew; Kumaran Jayaraj Vijaya; Leong Marieanne Christie (E3S Web of Conferences)
Royal Belum State Park (RBSP) is located north of Perak state. RBSP was gazette under the Enactment of National Forestry Act 1984. RBSP is notably rich in biodiversity and is home to endemic species for various flora and fauna that are susceptible to climate change. This study explores the precipitation of RBSP that can be the guideline for mitigation plan. The precipitation data from CHIRPS and PERSIANN-CCS datasets were analyzed to act as observation data against historical data from Coordinated Regional Downscaling Experiment – Southeast Asia (CORDEX-SEA). The future precipitation of RBSP is assessed by using the simulation model from CORDEX-SEA. The future emission scenarios used in this study are Representative Concentration Pathways (RCP) 4.5, and 8.5. The future projection from this study can be used to provide the mitigation and adaptation plan catered for RBSP. The limitation of this study is the model output are focused on Peninsular Malaysia. Further study may benefit from analysing localized model that integrate the local topography and land process.